When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.
If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3
Are you asking me to tell you the answer? Because its easy and simple .
if it is not this . -3<x<-2 < or equal
The sum of a number plus 3 to the square root of 9 to the sum of 2 would equal -2. This is a math problem.
If you mean: (x+3)^2 = (x+2)^2 +13 Then the value of the number x works out as 4
A squared plus b squared equils c squared
[(x+3)^2] - [(x+2)^2] = 13 ==> 2x = 8 ==> x = 4. the number is 4!
(x + 3)2 = (x + 2)2 + 9 x2 + 6x + 9 = x2 + 4x + 4 + 9 2x = 4 x = 2
A number is x squared plus forty four is equal to the number x to the fourth power times three?
25 squared plus 49 squared is equal to 3,026.
Since a squared plus b squared equals c squared, that is the same as c equals the square root of a squared plus b squared. This can be taken into squaring and square roots to infinity and still equal c, as long as there is the same number of squaring and square roots in the problem. Since this question asks for a and b squared three times, and also three square roots of a and b both, they equal c. Basically, they cancel each other out.
6 squared plus 9 squared is equal to 117.
12 squared plus 18 squared is equal to 468.
7 Squared is 49. 10 plus 49 is 59.